Real Time Medical Image Consultation System Through Internet. Issue 1 (2010) - Prasad, D. Durga; Ray, Saikat; Majumdar, Arun K.; Mukherjee, Jayanta; Majumdar, Bandana; Paul, Soubhik; Verma, Amit
Abstract : Teleconsultation among doctors using a telemedicine system typically involves dealing with and sharing medical images of the patients. This paper describes a software tool written in Java which enables the participating doctors to view medical images such as blood slides, X-Ray, USG, ECG etc. online and even allows them to mark and/or zoom specific areas. It is a multi-party secure image communication system tool that can be used by doctors and medical consultants over the Internet.